Express.js Deep API Reference - Mardan, Azat.; SpringerLink (Online service) (Berkeley, CA : Apress : Imprint: Apress, 2014)
Express.js Deep API Reference is your short, concise guide to Express.js APIs. This flexible Node.js web application framework provides a robust set of features for building single, multi-page, and hybrid web applications. Through six to-the-point chapters, you will find references for configurations, settings, environments, middleware, templating engines (including Consolidate.js), extract parameters, routing, request handlers, response, and streams. Written by Azat Mardan, the author of Pro Express.js and Practical Node.js, you will find this short, concise guide indispensable for your Express.js work.
Keywords: Computer programming; Software engineering; Web Development; Software Engineering/Programming and Operating Systems